Assessment of genetic divergence in rice (Oryza sativa L.) germplasm using D2 analysis - Vinayak V. Thakare; G.M. Lal; Bineeta M. Bara (Annals of Agricultural Research, 2025)
The present investigation was conducted with 41 genotypes of Rice during Kharif 2023 in randomized block design (RBD) with three replications. The 41 rice genotypes were characterized based on 13 quantitative traits viz, days to 50 per cent flowering, days to maturity, flag leaf length, flag leaf width, the total number of effective tillers per plant, plant height (cm), panicle length (cm), the number of spikelets per panicle, biological yield, grain yield per plant, test weight, harvest index, using Mahalanobis D2 statistics. D2 analysis distributed the 41 genotypes into six clusters, of which cluster I was the largest with 36 genotypes. Lowest inter cluster distance was between cluster I and cluster IV which was 60.58, and highest inter cluster distance was between the cluster IV and cluster VI which was 247.17,Therefore genotypes present in these clusters should be used for the future hybridization program.